PHYSICOCHEMICAL PROPERTIES OF ACHA-PEANUT COMPOSITE FLOUR ENRICHED WITH CARROT AND ORANGE-FLESHED SWEET POTATO - Sule, Stephen (Food and Feed Research, 2024)
Physicochemical characteristics of acha-peanut composite flour separately enriched with carrot and orange-fleshed sweet potato(OFSP) flours, yielding four samples based on a 19g protein target were assessed: A (100% acha), AP (81.08% acha + 18.92% peanut), APC (64.21% acha + 20.64% peanut + 15.15% carrot), and APO (64.55% acha + 20.74% peanut + 14.71% OFSP). Sample APO had significantly (p<0.05) higher protein content (19.72%), while AP had higher fat (3.54%). APC had higher ash (3.14%), fibre (5.08%), and energy (388.37 kcal) values, whereas sample A had higher carbohydrate (79.95%). Sample APC had significant (p<0.05) higher differences observed in bulk density (0.82 g/ml), water absorption (1.56 g/g), oil absorption (1.47 g/g), and swelling index (3.01). APC also had the lowest peak (366.10 RVU), trough (167.50 RVU), breakdown (199.80 RVU), final (393.20 RVU), and setback (244.30 RVU) viscosities, while sample A had the lowest peak temperature (59.12°C) and peak time (5.36 min). APC contained higher calcium (21.12 mg/100g), magnesium (72.64 mg/100g), iron (9.07 mg/100g), zinc (3.96 mg/100g), and beta-carotene (6.75 mg/100g), whereas sample A had higher thiamine (0.41 mg/100g), and APO had higher vitamin C (3.11 mg/100g). Antinutrient contents ranged from 0.12-1.02 mg/100g, 0.13-0.90 mg/100g, 0.14-0.32 mg/100g and 0.22-0.61 mg/100g for tannins, phytates, oxalates and trypsin inhibitors, respectively. APC had the lowest tannin and phytate values, while lower oxalates and trypsin inhibitors were found in samples A and APO, respectively. These findings underscore the potential of these composite flours in improving dietary quality and addressing nutrient deficiencies, particularly for children.